CORONARY ARTERY ANOMALY. CORONARY-PULMONARY FISTULA - S. V. Topilina; E. I. Zyablova; A. M. Namitokov; E. D. Kosmacheva (Инновационная медицина Кубани)
True coronary and pulmonary fistulas occur quite seldom. Most often this defect is a casual finding at diagnosis of other cardiac diseases. Hemodynamics of this defect is caused by the affected coronary artery shunt into the cardiac chamber or the great vessel. Before introduction in modern diagnosis methods of high-precision ultrasonic devices and cardiac treatment to verify such anomaly as a coronary artery fistula, it was impossible. In our study we present a clinical case with right and left coronary artery fistulas into a pulmonary artery and a left atrium.